Knowledge, Attitude, and Practices Toward Tuberculosis Among Hospital Outpatients in Kabul, Afghanistan - Essar, Mohammad Yasir; Rezayee, Khalid Jan; Ahmad, Shoaib; Kamal, Manar Ahmed; Nasery, Reshaduddin; Danishmand, Tamim Jan; Head, Michael; Nemat, Arash (Frontiers in Public Health, 2022)
Background Tuberculosis (TB) is a high-burden respiratory infectious disease. There was a sharp decline in the number of confirmed TB cases during the pandemic; this is likely to be influenced by the COVID-19 pandemic response, with under-reporting due to resource diversion. There are typically 13,000 tuberculosis-associated deaths in Afghanistan annually, with significant problems posed by drug-resistant TB. Method A cross-sectional descriptive study was conducted in Afghanistan on Kabul residents who visited the adult outpatient departments of public hospitals for any health-related reason from 1st January to 20th March 2022. The study scored their knowledge, attitude, and practices (KAP) toward tuberculosis. The sample size was calculated using Epi-Info, and the minimum sample size was 385. The sampling method is chosen the non-probability convenient sampling for data gathering. Data were analyzed using SPSS version 28, and we used the Mann-Whitney test, Chi-square or fisher extract test, spearman correlations, and binary logistic regression model. Results Of 829 participants, 450 (54.3%) were males and 379 (45.7) females. The median age was 28 years, and 63.3% were married. Most participants were unemployed (75.5%), but 54% had a monthly income >3,000 Afghanis, indicating the reliance on family. By TB knowledge score, 727 (87.7%) participants had good knowledge, and 800 (96.5%) participants had a positive attitude toward treatment and control. Only 2 participants reported poor practices regarding prevention. Regarding the binary logistic regression, young age, being a male, belonging to the “1,000–3,000” Afghani monthly income category, and having a positive attitude were significant predictors of good TB knowledge (P-value = 0.009, 0.000, 0.003, and 0.009), respectively. A positive attitude was expected to have good knowledge 6.035 times more than a negative attitude (95% CI: 1.572–23.167). Conclusion The study findings highlighted that outpatients in Kabul had good knowledge, attitude, and practice toward TB. More studies are needed to highlight KAP in different Afghan populations, including in other parts of the country.